2021
DOI: 10.1080/14763141.2021.1919750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body position and mass centre velocity at toe off on the start performance of elite swimmers and how this differs between gender

Abstract: The start in swimming is a crucial phase of a race, where improvements in performance can be made. Twenty-four elite swimmers race pace starts were recorded from five above and below water 50 Hz video cameras. Body position at toe off was calculated from the recordings and consisted of the two-dimensional mass centre position at toe off, and the arm, trunk, front leg and rear leg angles. Horizontal, vertical and resultant velocity of the mass centre at toe off, time to 5 m, 10 m and 15 m were also determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The advantages provided by OSB starting blocks or their platforms lie in the rear support and its adjustment, which allows displacement in five positions. This change in the start block has led to some research [ 2 , 4 , 6 , 7 , 12 , 13 , 20 ], which have addressed the adjustment of the backrest or the change of the base position on the start block, which affect the kinematic–dynamic parameters in the on-start block phase, the kinematic parameters in the flight and underwater phases, as well as the take-off performance itself. For example, a study by Cicenia et al [ 21 ] looked at the use of shin length as a measure to determine cleat position and its effect on performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages provided by OSB starting blocks or their platforms lie in the rear support and its adjustment, which allows displacement in five positions. This change in the start block has led to some research [ 2 , 4 , 6 , 7 , 12 , 13 , 20 ], which have addressed the adjustment of the backrest or the change of the base position on the start block, which affect the kinematic–dynamic parameters in the on-start block phase, the kinematic parameters in the flight and underwater phases, as well as the take-off performance itself. For example, a study by Cicenia et al [ 21 ] looked at the use of shin length as a measure to determine cleat position and its effect on performance.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study indicated that shin length is a quick and individualized measure that coaches can use to determine kicking plate position without compromising performance. A study by Shepherd et al [ 7 ] demonstrated that rebounding body position does not differ for the two genders but is a critical factor in determining initial performance for both genders. Barlow et al [ 1 ] and Matúš and Kandráč [ 5 ] reported the best performance when the kick plate is at the third and fourth level, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation